CONCENTRATE OF MOLECULAR IODINE DETECTION WITH PORTABLE COLORIMETER ON POLYURETHANE FOAM: UDC 543.432'831 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
The possibility to use the portable photometer for registering color characteristics of the polyurethane foam (PUF) was studied. For the system I2-PUF was plotted calibration curve: dependence of the intensity of the B color channel from the amount of iodine in the sample. Construction of calibration dependences was performed in the following way. In syringes was taken from 0,25 to 10,0 cm3 of a standard solution of iodine with a concentration of 1,2 mg/dm3 (pH~2) and sulfate acid (pH~2) to a total volume of 10,0 cm3, stirred, removed the iodine on surface of PUF, and recorded the analytical signal at 370 nm with two method relative to pure tablets sorbent. To build a calibration curve with iodide carried out a preliminary oxidation of iodide to I2 using oxone. The dependence of the analytical signal of iodine on the surface of the sorbent using a portable photometer described by the equation y=1,32+0,92.10-4.с (mg/dm3), R2=0,998, where y – the analytical signal B-channel. The results for iodine PUF and colorimetric methods solid-phase spectrophotometry almost the same. Range of linearity calibration curve is wider in the case of colorimetric detection. The results of determination supplementation of I2 and I- to bottled drinking water using a portable photometer. Established that confidence interval changes from the maximum value for ±9,7 % с(І2)=0,1 mg/dm3 to a minimum for ±6,0 % с(І2)=1,0 mg/dm3 (n=5, P=0,95). Portable colorimeter due to its sensitivity and accuracy promising and convenient for use in situ (at sampling site).
Keywords: iodine, iodide, polyurethane foam, portable photometer, solid-phase spectrophotometry